Legal Interpretation: Critical Reasoning for the Development of an Islamic Paradigm that is Friendly to Women And Children - Sukadi, Imam; Ratomi, Achmad; Ningsih, Mila Rahayu (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 1 (2021): The 4th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2021)
At this time there are still many misinterpretations about the teachings of Islam that related to the position of women and children. Cultural construction and interpretation of religious experts who use inappropriate mindsets in viewing and understanding religious texts is also a crucial factor as the cause of inequality in relations between groups in the social order of Muslims. The characteristics of Islamic teachings are also humanist, which can be seen from the efforts to protect human rights as can be seen in terms of their vision, mission, and goals. Islamic teachings in the context of granting human rights to women, fully recognize and respect the position of women as creatures of Allah SWT. Islam has removed all forms of injustice that befell women and raised their status as human dignity. Islam does not limit and restrain women's steps in developing their potential. In the context of providing protection and rights for children, the seriousness of Islam in dealing with the status of children is increasingly legitimate with the many verses of the Al-Qur’an that discuss the status of children. Islam's alignment with child protection is a priority. The instruments related to this seem to have been neatly arranged to create a generation of good and compassionate people.